The effect of large crypto platform crashes on the volatility of the crypto market. - Valatina, Ekaterina; Jedlinský, Jakub; Abdallah, Kareem Issam; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
The thesis explores four major crypto exchange platform crashes – Mount Gox, Celsius Network, Terra Luna and FTX. The findings suggest that application of econometric GARCH and VAR modelling, using crypto assets issued by the crypto exchange platforms as a proxy for measuring volatility with varying results of success. All crypto exchange platform crashes have shown to have a large, negative short-term effect on the crypto market’s volatility and market capitalization. The volatility caused by the devaluation of crypto assets has ranged between 0.00% and 50.51%, as well as assessing the total economic impact on the crypto market evaluation to be $2.2 Trillion during the year 2022. The analysis identified varying degrees of causality between the crypto assets issued by the crypto exchanges and related crypto assets,however, the data structure may impede results due to sudden nature of crashes, requiring more contextual information to interpret the results to align with the real effects. The crypto market demonstrates considerable resilience to volatility, as the market absorbs shocks within a 6-month period.
Vedoucí práce: Jakub Jedlinský
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses